Recent Advances in Studying Age-Associated Lipids Alterations and Dietary Interventions in Mammals - Gille, Benedikt; Galuska, Christina E.; Fuchs, Beate; Peleg, Shahaf (Frontiers in Aging, 2021)
Lipids are involved in a broad spectrum of canonical biological functions, from energy supply and storage by triacylglycerols to membrane formation by sphingolipids, phospholipids and glycolipids. Because of this wide range of functions, there is an overlap between age-associated processes and lipid pathways. Lipidome analysis revealed age-related changes in the lipid composition of various tissues in mice and humans, which were also influenced by diet and gender. Some changes in the lipid profile can be linked to the onset of age-related neurodegenerative diseases like Alzheimer’s disease. Furthermore, the excessive accumulation of lipid storage organelles, lipid droplets, has significant implications for the development of inflammaging and non-communicable age-related diseases. Dietary interventions such as caloric restriction, time-restrictive eating, and lipid supplementation have been shown to improve pertinent health metrics or even extend life span and thus modulate aging processes.